Analisis Kadar Vitamin A pada Minyak Goreng Sawit dengan Metode HPLC (High Performance Liquid Chromatography) - Suci Asaumi; Minda Azhar (MASALIQ, 2025)
This study is motivated by the importance of vitamin A content in palm cooking oil as an effort to prevent vitamin A deficiency in the community. The objective is to measure the vitamin A content in palm cooking oil using the High Performance Liquid Chromatography (HPLC) method in accordance with SNI 7709-2019. Samples of palm cooking oil were obtained from a store on Jl. Sail, with the analytical procedure involving the preparation of standard vitamin A solutions in acetone and ethanol, the addition of pyrogallol acid as an antioxidant, saponification with 50% KOH, and the addition of glacial acetic acid to improve extraction efficiency. HPLC analysis was conducted using a mobile phase of methanol–aquabidest (860:140) and THF–ethanol (50:50) as the solvent. The chromatogram showed a vitamin A peak at a retention time of approximately 11.40 minutes. The calculated results indicated an average vitamin A content of 1,095.32 IU/g, far exceeding the minimum limit of 45 IU/g as required by the quality standard for palm cooking oil. The study concludes that the HPLC method with this procedure can accurately measure vitamin A content, and the tested palm cooking oil samples meet the vitamin A standard for public consumption.